Optimizing a redundancy allocation problem with open-circuit and short-circuit failure modes at the component and subsystem levels. Issue 6 (3rd June 2021) - Sharifi, Mani; Taghipour, Sharareh
Abstract : In failure-prone systems, it is important to take into considerations all the failure modes of each component to achieve the optimal system reliability. In this paper, a new series-parallel redundancy allocation problem is presented for a system in which the subsystems and components are subject to two different independent failure modes: short-circuit and open-circuit. It is assumed when a pre-determined number of a subsystem's components fail due to short- or open-circuit failure types, the subsystem fails. Moreover, when more than a pre-determined number of the system's subsystems fail due to short- or open-circuit failure types, the system fails. A new method based on the universal generating function is used to calculate the system's short-circuit failure probability, and the results are validated with the Monte-Carlo simulation. Then, a mathematical model for the considered RAP is presented to maximize the system's reliability. Finally, the proposed model is solved using a genetic algorithm.